The Effect of Creative Drama on Attitudes towards Turkish Lessons and Turkish Language Skills: A Meta-Analysis Study - Perihan Gülce Özkaya (Mehmet KURUDAYIOĞLU, 2022)
The purpose of the current study is to determine the effect of creative drama on the attitudes of students from different levels of education in Turkey towards Turkish lessons and Turkish language skills. To this end, a meta-analysis of the studies examining the effect of creative drama on the attitudes towards Turkish lessons and Turkish language skills was conducted. Within the context of the study, it was also tried to determine whether the effect values vary depending on the type of publication, the education level of the participants, and the domain of attitude moderator variables. A total of 17 studies were included in the meta-analysis study. The sample size of the studies included in the meta-analysis was 733 people, including 424 participants in the experimental group and 309 participants in the control group. The studies included in the meta-analysis are heterogeneous. In addition to the publication bias result of the funnel plot, Orwin's Safe N analysis, Duval and Tweedie's Trim and Fill and Egger's regression analysis revealed no publication bias. Effect values were calculated according to the random effects model. Cohen's d coefficient was used in the effect value calculations. The Q test and p significance coefficient were used to determine the moderator variable effect. In the study, it was determined that creative drama has a positive and high level effect on the attitudes towards Turkish lessons and Turkish language skills. When the results of the moderator variable analysis were examined, it was seen that the variance between studies for the moderator variable of publication type was not significant in terms of the attitudes towards Turkish lessons and Turkish language skills while it was significant in favor of high school level for the moderator variable of education level and in favor of speaking skill for the moderator variable of domain of attitude.